Предмет: Алгебра,
автор: ekaterina199891
помогите пожалуйста (m^2+3m/m^2+3m-4 - m^2-4m/m^2-4m+3) / m/m^2+m-12
Ответы
Автор ответа:
0
1)(m²+3m)/(m-1)(m+4)-(m²-4m)/(m-1)(m-3)=
=[m(m+3)(m-3)-m(m-4)(m+4)]/(m-1)(m+4)(m-3)=
=[m(m²-9)-m(m²-16)]/(m-1)(m+4)(m-3)=
=m(m²-9-m²+16)/(m-1)(m+4)(m-3)=7m/(m-1)(m+4)(m-3)
2)7m/(m-1)(m+4)(m-3) : m/(m+4)(m-3)=
=7m/(m-1)(m+4)(m-3)*(m+4)(m-3)/m=7/(m-1)
=[m(m+3)(m-3)-m(m-4)(m+4)]/(m-1)(m+4)(m-3)=
=[m(m²-9)-m(m²-16)]/(m-1)(m+4)(m-3)=
=m(m²-9-m²+16)/(m-1)(m+4)(m-3)=7m/(m-1)(m+4)(m-3)
2)7m/(m-1)(m+4)(m-3) : m/(m+4)(m-3)=
=7m/(m-1)(m+4)(m-3)*(m+4)(m-3)/m=7/(m-1)
Похожие вопросы
Предмет: МХК,
автор: litvir87
Предмет: Математика,
автор: catskotik
Предмет: Математика,
автор: albinamuldabekova278
Предмет: История,
автор: Annlove04